Visual Depiction And Transformation Of Time And Space Through Landscape Abstraction - Wei, Jinqin (2024)
Time is never-ending, while space is created by the positioning of objects and the changes that occur with their movement. Landscapes are essentially all-encompassing, changing, and transient with the passage of time. The word “transient” is of Buddhist origin and suggests the changing state of everything in the world, which affects all aspects of human activity and the environment. The concept of the Japanese tea ceremony involving “one period, one encounter” originates from Chinese Zen Buddhism, which has conducted a fundamental exploration of “transient” and developed a philosophical context for studio practice research. Based on the philosophical context of transience and guided by two theories of spatio-temporal relations, ‘endurantism’ and ‘perdurantism’, this research incorporates Guo Xi’s ‘three distances’ method of observation, color symbolism, and Graham Gibbs’s Reflective Cycle into a studio practice to investigate how the relationship between time and space can be visually depicted and transformed through landscape abstraction. This study relies on years of personal experience and transient context to generate a personal understanding of the possibility that spatio-temporal relationships. This research suggests that time affects the real presence of landscape space, making it an abstract form of stillness, ambiguity, or change (conceptualized respectively as “freezing the moment,” “instantaneous blur,” and “time change”), thus making a new contribution to studio practice.